INVESTMENT ECONOMY IN IRRIGATION SYSTEM IN CLIMATIC CONDITIONS IN RASPBERRY REGION OF ARILJE AREA - Cecić, Nataša; Milivojević, Jordan; Arsić, Slavica (Economics of Agriculture, 2006)
Тhis work have analysed climatic water balance in Raspberry region of Arilje in vegetative cycle of raspberry, in function of yield fluctuation in natural condition and irrigation water balance regime of soil and economical payable for introduction of irrigation in raspberry production. Introduction of irrigation, raspberry yields can be increased in average 1,8- 3,3 times in relation to yield without irrigation, and investment in mini-irrigation system construction, on surface for just one plant, with water supporting from local watercourse can be pay off for one growing season. Raspberry reacts on irrigation with increasing yield in such a level that it is profitable to invest in mini-irrigation system construction every year again.